Factors affecting school performance: Does a mixed curriculum make a difference? - Stefy Falentino Akuba; Poltak Sinaga; Gracia Shinta S Ugut; Sidik Budiono (Jurnal Cakrawala Pendidikan, 2021)
This article reports on a study that attempts to fill the gap of research focusing on school performance measurements, especially those which involve curriculum types. It established the factors that measured school performance using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) and analyzed any differences in the performance of schools adopting national curriculum and those adopting mixed curriculum in Greater Jakarta. From 29 items, eight invalid items were dropped, and the EFA identified eight factors, which were categorized into social-emotional learning, school participation, relationship, physical-mental health, physical safety, emotional safety, academic growth, and discipline. Then, the scale was validated using data collected from 684 secondary students using CFA. Chi-square goodness-of-fit test was not statistically significant. However, other indices such as Incremental Fit Index, Comparative Fit Index, Tucker-Lewis Index, Root Mean Squared Error of Approximation, and Standardized Root Mean Square Residual were within acceptable limits, indicating that the eight EFA factors had been validated. Moreover, this study found that schools with mixed curricula had higher performance than those with a national curriculum. Nevertheless, it cannot be generalized because the linear regression shows that the p-value was higher than 0.05 (0.164).